Comprometimento do trabalhador e estilos de liderança - Monastersky, Roberto (2022)
This thesis aims to demonstrate that proving that the leadership is responsible for the commitment of the worker with his work activities and with the strategic objectives of the companies. The study suggests that hierarchical authority structures provide for the existence of bosses whose role is to exercise control over the workforce and seek subterfuges to increase productivity and profits. Unlike leaders, these bosses do not support workers in developing entrepreneurial behavior, nor in meeting their needs for self-esteem and self-fulfillment through work. This thesis is based on the studies of work sociology and organizational psychology, which emphasize that the combination of different leadership styles can promote the personal and professional development of workers and, therefore, serve to increase productivity in business organizations. The exploratory research was carried out in 10 fintechs that are micro and small companies, that is, startups that work for the innovation and optimization of the financial system. The term fintech is the result of the union of the English language words financial and technology, that is, finance and technology. On the occasion, 30 workers, 10 leaders and 20 led were interviewed. The answers provided by the interviewees prove the veracity of the study's guiding hypothesis: there is an increase in commitment when leadership styles allow the worker's personal and professional growth